Efektivitas Media Pembelajaran berbasis Gamifikasi Zeepquiz dalam Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Fikih - Padli Dwi Herlambang; Nur Hidayat Nurhidayat; Ahmad Zacky Burhani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
The purpose of this study was to determine the effectiveness of Zeep Quiz, a gamification-based learning media, in increasing students' learning engagement in Islamic jurisprudence. This study was conducted using the Classroom Action Research (CAR) method, which has a spiral model that includes planning, implementation, observation, and reflection stages. Students enrolled in grade XI of Madrasah Aliyah Miftahul Jannah in the 2025/2026 academic year were the subjects of the study. To collect data, observation, interviews, and documentation were used, and to analyze it, quantitative and qualitative descriptive approaches were used. The research results show that Zeep Quiz can increase student learning engagement. At the beginning of the cycle, students were considered less active in learning. However, after interventions were taken during Cycle I, students began to learn more, met success indicators, and became more engaged in discussions and learning activities in Cycle II. Therefore, the use of Zeep Quiz, a gamification-based learning tool, has shown that students are more engaged in Islamic jurisprudence (Fiqh) lessons and have the ability to create a more engaging, interactive, and enjoyable learning environment. Furthermore, using Zeep Quiz makes students' learning experiences more meaningful, making it an attractive option.